Building business resiliency through control system principles - Moscato, Donald R. (Henry Stewart Talks, 2011)
Resiliency, Reliability, Control mechanisms, Principles of management, Risk management, Threats to systems requiring controls, Preventive, detective and corrective controls, Zero trust networking model, Signals as triggers, Importance of feedback, Servomechanism, Cybernetics, Law of requisite variety, The role of granularity and redundancy in control systems, Beer's classification, Hare's systems hierarchy, Network controls, Application controls, Auditing systems involving the computer, Regulatory compliance as a controls component, Control testing